THE RATE OF CONTAMINATION OF UPPER AIRWAYS WITH HUMAN PAPILLOMA VIRUSES IN CHILDREN - Yu.L. Soldatskiy; E.K. Onufrieva; Yu.V. Strygina; I.E. Pogosova; A.V. Dyudya ("Paediatrician" Publishers LLC, 2009)
This trial studied the rate of contamination of mucous tunica of throat, nasopharyngeal and palatine tonsils with human papilloma viruses, type 6, 11, 16, 18, 31 and 33. 29 children with recurrent respiratory papillomatosis (RRP) and 57 children hospitalized for planned adenotomy, tonsillotomy or tonsillectomy took part in this trial. Virus in bioptate from removed papillomas was discovered in 100% of patients with RRP (type 6 and (or) 11 in all cases). Despite absence of clinical symptoms of throat papillomatosis, contamination of mucous tunic of throat was discovered in 48% of patients in this group. Children without clinical signs of RRP had virus contamination of upper airways in 44% cases. The rate of contamination of schoolchildren and younger children was comparable.Key words: children, human papilloma virus, recurrent respiratory papillomatosis.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):20-24)